EDMODO AS A MEDIA TO TEACH VOCABULARY - Sutrisno Evenddy; Welliam Hamer (English Department - University of Sultan Ageng Tirtayasa, 2016)
This article aims at intoducing how to use Edmodo to teach vocabulary. Vocabulary is a component of English language. When we are speaking and writing, we need to master vocabulary related to certain topic. Therefore vocabulary is important thing in learning language. But, mastering English vocabularies is not easy. Teacher needs a media to make an interesting teaching-learning process. One of the most accepted trends in the field of teaching vocabulary in a foreign language teaching is Computer-Assisted Language Learning (CALL). CALL has several applications that can be used by the teachers in teaching vocabulary. Computer and mobile telephone internet allow immediate connection to a server. In the internet browser the teachers and students can browse Edmodo. One of media is Edmodo. Edmodo is one of social media which can be operated by students, teachers or lecturers, and parents. It is able to be used to post various assignments and students’ learning achievement, actual discussion topics, video, appointments, and to facilitate students’ polls which are related to teaching learning process.